Neural Basis of Depression Related to a Dominant Right Hemisphere: A Resting-State fMRI Study - Mi Li; Hongpei Xu; Shengfu Lu (Behavioural Neurology)
Background. In the past, studies on the lateralization of the left and right hemispheres of the brain suggested that depression is dominated by the right hemisphere of the brain, but the neural basis of this theory remains unclear. Method. Functional magnetic resonance imaging of the brain was performed in 22 depressive patients and 15 healthy controls. The differences in the mean values of the regional homogeneity (ReHo) of two groups were compared, and the low-frequency amplitudes of these differential brain regions were compared. Results. The results show that compared with healthy subjects, depressive patients had increased ReHo values in the right superior temporal gyrus, right middle temporal gyrus, left inferior temporal gyrus, left middle temporal gyrus, right middle frontal gyrus, triangular part of the right inferior frontal gyrus, orbital part of the right inferior frontal gyrus, right superior occipital gyrus, right middle occipital gyrus, bilateral anterior cingulate, and paracingulate gyri; reduced ReHo values were seen in the right fusiform gyrus, left middle occipital gyrus, left lingual gyrus, and left inferior parietal except in the supramarginal and angular gyri. Conclusions. The results show that regional homogeneity mainly occurs in the right brain, and the overall performance of the brain is such that right hemisphere synchronization is enhanced while left hemisphere synchronization is weakened. ReHo abnormalities in the resting state can predict abnormalities in individual neurological activities that reflect changes in the structure and function of the brain; abnormalities shown with this indicator are the neuronal basis for the phenomenon that the right hemisphere of the brain has a dominant effect on depression.